Perspectives on early insights: pediatric cancer caregiving amidst natural calamities – A call for future preparedness - Rizzi, Damiano; Ciuffo, Giulia; El Gour, Firdaous; Erradi, Jinane; Barone, Lavinia; Ionio, Chiara (Frontiers in Public Health, 2024)
Natural disasters cause immense damage and disruption to the environment, human lives, and property, posing a threat to safety and well-being. These disasters annually affect individuals and communities, severely impacting mental health. Research indicates a significant link between catastrophic events and an increased risk of mental disorders, including anxiety, depression, substance use, and post-traumatic stress disorder (PTSD). Individuals with chronic conditions, like cancer patients, are particularly vulnerable post-disaster due to disrupted healthcare services. The recent earthquake in Morocco highlighted the urgent need for continued care, especially for vulnerable populations living in poverty. Soleterre Foundation’s interventions focus on supporting young cancer patients and their families, emphasizing psychological support following the earthquake. Effective disaster response needs coordinated efforts, clear roles, communication, and standardized healthcare procedures, especially for vulnerable groups like cancer patients. Education programs for patients and clinicians are vital for disaster preparedness. Communication challenges and lack of medical history further emphasize the need for well-defined disaster preparedness plans and continued care guidelines for cancer patients.